2010
DOI: 10.1126/scitranslmed.3000813
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Role of WASp in the Pathogenesis of Dysregulated T H 1 Immunity in Human Wiskott-Aldrich Syndrome

Abstract: The clinical symptomatology in the X-linked Wiskott-Aldrich syndrome (WAS), a combined immunodeficiency and autoimmune disease resulting from WAS protein (WASp) deficiency, reflects the underlying coexistence of an impaired T helper 1 (T H 1) immunity alongside intact T H 2 immunity. This suggests a role for WASp in patterning T H subtype immunity, yet the molecular basis for the T H 1-T H 2 imbalance in human WAS is unknown. We have discovered a nuclear role for WASp in the transcriptional regulation of the T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
147
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(153 citation statements)
references
References 65 publications
4
147
1
1
Order By: Relevance
“…Nuclear N-WASP can regulate RNA-polymerase-II-dependent transcription through a direct interaction with the PSF-NonO (polypyrimidinetract-binding-protein-associated splicing factor-non-Pou-domain octamer-binding protein, also known as p54 nrb ) complex, and this process is associated with polymerization of actin (Wu et al, 2006). By contrast, nuclear WASP modulates the transcription of the T helper 1 (T H 1) regulator gene TBX21 by association with H3K4 trimethyltransferase and H3K9/H3K36 tridemethylase, which is independent of Arp2/3-dependent actin polymerization (Sadhukhan et al, 2014;Taylor et al, 2010). A recent report has demonstrated that nuclear WAVE1 is required for transcriptional reprogramming in oocytes and embryonic development (Miyamoto et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nuclear N-WASP can regulate RNA-polymerase-II-dependent transcription through a direct interaction with the PSF-NonO (polypyrimidinetract-binding-protein-associated splicing factor-non-Pou-domain octamer-binding protein, also known as p54 nrb ) complex, and this process is associated with polymerization of actin (Wu et al, 2006). By contrast, nuclear WASP modulates the transcription of the T helper 1 (T H 1) regulator gene TBX21 by association with H3K4 trimethyltransferase and H3K9/H3K36 tridemethylase, which is independent of Arp2/3-dependent actin polymerization (Sadhukhan et al, 2014;Taylor et al, 2010). A recent report has demonstrated that nuclear WAVE1 is required for transcriptional reprogramming in oocytes and embryonic development (Miyamoto et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, our data show that FAM21 can interact with the promoter regions of key NF-kB target genes and that loss of FAM21 results in decreased p65 chromatin loading. It is noteworthy that other actin NPFs such as JMY, WASP, neuronal WASP (N-WASP) and WAVE1 have previously been observed in the nucleus and involved in gene transcription Miyamoto et al, 2013;Sadhukhan et al, 2014;Taylor et al, 2010;Wu et al, 2006;Zuchero et al, 2009). Nuclear N-WASP can regulate RNA-polymerase-II-dependent transcription through a direct interaction with the PSF-NonO (polypyrimidinetract-binding-protein-associated splicing factor-non-Pou-domain octamer-binding protein, also known as p54 nrb ) complex, and this process is associated with polymerization of actin (Wu et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In apparent contrast with our findings, a role for WASP in the nucleus of T cells has been recently established, showing that it controls the transcriptional regulation of T-bet at the chromatin level. 17 We, therefore, need to consider that WASP may play parallel but non-redundant roles in distinct intracellular compartments, converging towards a fine-tuning of key signaling pathways and transcriptional programs. …”
Section: Discussionmentioning
confidence: 99%
“…16 However, the role of WASP at the IS has been further challenged by the discovery that this protein can also be present in the nucleus, where it participates in the regulation of cytokine gene transcription. 17 In this context, the real-time observation of WASP-deficient T cells contacting APC is still missing and would help to elucidate whether WASP links IS dynamics and architecture to downstream T-cell signaling and activation.…”
Section: Introductionmentioning
confidence: 99%
“…In the absence of WASP, T-helper (T H 0) cells primarily developed into T H 2 cells, which are more prone to promoting autoimmunity. They showed that WASP accumulates in the nucleus of T H 0 cells that have been activated through their T-cell receptor and stimulated to polarize toward a T H 1 phenotype, which is driven by the expression of the transcription factor T-BET (encoded by the TBX21 gene) (Taylor et al, 2010). WASP was found to associate with the TBX21 promoter, where it recruited the pre-initiation complex, chromatin-remodeling factors and subunits of the SWI/SNF CRC Taylor et al, 2010).…”
Section: Wasp Family Proteins In the Nucleus Waspmentioning
confidence: 99%